IMPLEMENTASI APLIKASI PRESENSI SIMPEGNAS SEBAGAI PENGGANTI E-ABSENSI DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA DUMAI - Siti Indah Rahmawati; Eka Putri Rahayu; Murni; Erinaldi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine how the implementation of the SIMPEGNAS Attendance Application as a replacement for the e-attendance system improves employee discipline at the Dumai City Women's Empowerment and Child Protection Office and to identify obstacles encountered in its implementation. This application uses an Android phone with facial recognition and location (GPS) features, so that attendance data is recorded in real time, accurately, and cannot be manipulated. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The theory used is the implementation theory of George Edward III which consists of 4 indicators: Communication, Resources, Disposition and Bureaucracy. The results show that the implementation of the SIMPEGNAS Attendance Application has a positive impact on improving employee discipline and strengthening the principles of transparency and accountability in employee governance. From the communication aspect, policy socialization has been carried out, but employee technical understanding still needs to be improved. From the resource side, there are still obstacles such as limited devices and internet network disruptions. In the disposition aspect, the majority of employees have a positive attitude towards the new system, although some still experience difficulties adapting. Meanwhile, in terms of bureaucratic structure, implementation is supported by clear reporting and oversight mechanisms and integration with the National Civil Service Agency (BKN). Overall, the implementation of SIMPEGNAS is considered effective in improving employee discipline and attendance transparency, but it requires support from improved facilities, networks, and ongoing coaching for optimal implementation.